Walter B. Wriston and Kathryn Dineen Wriston in Florida (Tufts Archival Research Center, 2008)
5.9 x 4. This date is approximate. The print and digital image were created from 'File2801' from the CD titled 'Walter B. Wriston Photographs - CD 1'.